The Success Factors for Growing Health Tech Startups in Thailand - Kittipong Jeamwittayanukul; Sujira Vuthisopon (My University, 2022)
Startups have served as one of the Thai government’s mechanisms for promoting economic stability and growth. The health tech startup is a global trend toward new innovative industries. In Thailand, there are many health tech startups born each year. However, the healthcare business characteristic and business model differing from other businesses urge the need to understand the relevant factors of success. This knowledge can help you lower your chances of failing and enhance your chances of succeeding. The success elements that influence success, as well as the ones that are most crucial for health tech firms, were investigated in this study. This research used quantitative methodologies to create a systemic approach. The researchers used data from 240 samples to assess basic statistics and confirmatory second-order factor analysis based on the idea of latent variables in Structural Equation Modeling (SEM). It was found that health tech startups in Thailand can be successful because of 6 elements, which are government policy, startup support, human capital, market, finance, and culture. Culture is the most influential factor, followed by startup support, human capital, market, government policy, and finance. It's worth noting that tax relief and low-interest financing aren't high on the priority list. Internal elements such as entrepreneurial inspiration or knowledge, experience, and product prominence, on the other hand, take precedence.
Keywords: High tech; Entrepreneurship Studies and Influences